Cognitive and affective elements in collective guilt after the violent conflict - Jelić, Margareta; Penić, Sandra; Čorkalo Biruški, Dinka; Ajduković, Dean (2009)
Collective guilt has been recognised as an important indicator of relations between formerly conflicting groups. Assigning guilt for past wrongdoings solely to the outgroup (without accepting that the ingroup has also harmed the other group in the past) shows lack of readiness to reconcile, whereas acceptance of ingroup responsibility represents an important step towards reconstruction of intergroup social relations. Recent studies have focused only on collective guilt acceptance, defining positive emotions towards the outgroup (trust and empathy) as its antecedents. We believe that cognitive elements of both collective guilt assignment and acceptance are also important elements of this process. The aim of this study was to investigate cognitive and affective predictors of collective guilt on two conflicted groups. The study was conducted in Vukovar, on two ethnic groups, 15 years after the conflict between them. The sample consisted of 317 participants (198 Croats i 119 Serbs). Demographic data (age, gender, ethnic membership), level of traumatisation, positive and negative intergroup affect, justification of wrongdoings committed by the ingroup, and self report of the level of collective guilt assignment and acceptance were collected. Results show significantly higher levels of collective guilt assignment than acceptance in both groups, which is a typical post-conflict pattern of intergroup relations. Hierarchical regression analyses suggest that the effect of traumatisation level on collective guilt is completely mediated by cognitive processes (i. e. justification of the ingroup). Positive affect predicts collective guilt only until cognitive processes are entered into regression equation.
Projekt MZOS
ENG